2008
DOI: 10.3390/s8106235
|View full text |Cite
|
Sign up to set email alerts
|

APEX - the Hyperspectral ESA Airborne Prism Experiment

Abstract: The airborne ESA-APEX (Airborne Prism Experiment) hyperspectral mission simulator is described with its distinct specifications to provide high quality remote sensing data. The concept of an automatic calibration, performed in the Calibration Home Base (CHB) by using the Control Test Master (CTM), the In-Flight Calibration facility (IFC), quality flagging (QF) and specific processing in a dedicated Processing and Archiving Facility (PAF), and vicarious calibration experiments are presented. A preview on major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 54 publications
0
62
0
Order By: Relevance
“…Such data is only acquired on campaign basis from instruments such as APEX (Itten et al, 2008) or HySpex (Baumgartner et al, 2012). Since the surface reflectance has a large impact on the AMF, cf.…”
Section: Aerosol Profile and Propertiesmentioning
confidence: 99%
“…Such data is only acquired on campaign basis from instruments such as APEX (Itten et al, 2008) or HySpex (Baumgartner et al, 2012). Since the surface reflectance has a large impact on the AMF, cf.…”
Section: Aerosol Profile and Propertiesmentioning
confidence: 99%
“…In particular, the Airborne Visible/Infrared Imaging Spectrometer (AVIRIS) [26,27], designed and operated by the NASA Jet Propulsion Laboratory in California, has been used since the late 1980s in a large number of imaging spectroscopy experiments and field campaigns. Other airborne imaging spectrometers widely used in the last few years are HyMAP [28], the Compact Airborne Spectrographic Imager (CASI) [29] and the Airborne Prism Experiment (APEX) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Such viable a priori information will most certainly further improve estimation accuracy. Nevertheless, the automated CRASh approach as presented in this study showed the potential of a fully automated, image based retrieval of vital agroecosystem variables, and could be an important contribution towards the incorporation of land surface products in operational chains for upcoming high resolution airborne and spaceborne imaging spectrometers such as APEX [64], ARES [65,66], and EnMap [67]. [85] L = 0.5 [14]; a = 1.2 [14,55]; b = 0.04 [14]; X=0.08 [14]; β = 1 [86] …”
Section: Discussionmentioning
confidence: 99%